2018
DOI: 10.3892/ol.2018.8380
|View full text |Cite
|
Sign up to set email alerts
|

FPOA induces apoptosis in HeLa human cervical cancer cells through a caspase‑mediated pathway

Abstract: In the present study, the triterpenoid 3-acetoxylanosta-8,24-dien-21-oic acid (FPOA) was extracted from Fomitopsis pinicola. The aim of the present was to elucidate the mechanism of action of FPOA in HeLa cervical cancer cells. Cell viability was examined using an MTT assay and the morphological detection of apoptosis was conducted using DAPI staining. The rate of apoptosis was examined via Annexin V-FITC/PI double staining and the expression levels of apoptosis-associated proteins were determined by western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, previous studies have reported that TNF-α levels could significantly increase the gene expression of BAX and decrease the gene expression of Bcl-2 in human tumor cells 29 ; these results were consistent with the ELISA results for TNF-α in this study. Cleaved Caspase 3 is a key apoptotic protein, and its presence indicated that apoptosis had occurred in the tumor cells in this study 30 . Furthermore, cleaved caspase-3 levels significantly increased after EPA treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, previous studies have reported that TNF-α levels could significantly increase the gene expression of BAX and decrease the gene expression of Bcl-2 in human tumor cells 29 ; these results were consistent with the ELISA results for TNF-α in this study. Cleaved Caspase 3 is a key apoptotic protein, and its presence indicated that apoptosis had occurred in the tumor cells in this study 30 . Furthermore, cleaved caspase-3 levels significantly increased after EPA treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, previous studies have reported that TNF-α levels could signi cantly increase the expression of BAX genes decrease the expression of Bcl-2 gene in human tumor cells 29 ; these results were consistent with the ELISA results for TNF-α in this study. Caspases3 is a key apoptotic protein, its presence indicated that apoptosis had occurred in the tumor cells analyzed in this study 31 . In this study, the caspase3 levels signi cantly increased after EPA treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, the number of apoptotic cells was detected by flow cytometry. The total percentage of apoptotic cells was defined as the sum of both early apoptosis (annexin V-FITC positive, PI negative) and late apoptosis (annexin V-FITC PI-positive) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%